MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP IPAS MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA FLASHCARD KELAS IV SDN 095/I OLAK - Prya Aprilia Qomisatun; Asrial; Issaura Sherly Pamela (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the implementation of the Problem-Based Learning (PBL) model assisted by flashcard media to improve students' conceptual understanding in the IPAS subject for fourth-grade students at SDN 095/I Olak, as well as to describe the improvement in students' conceptual understanding after the implementation. This research is a Classroom Action Research (CAR) conducted in two cycles. Data were collected through observation, interviews, tests, and documentation. The results show an increase in students’ understanding of IPAS concepts, observed through several indicators: interpreting, giving examples, classifying, summarizing, concluding, comparing, and explaining. The improvement occurred gradually from Cycle I to Cycle II through the application of the PBL model with flashcard support. In Cycle I, the first meeting showed a percentage of 40% of students achieving conceptual understanding, which increased to 54.54% in the second meeting. In Cycle II, the percentage rose to 58.33% in the first meeting and reached 83.33% in the second meeting. This indicates a total improvement of 43.33% from the beginning to the end of the study. These findings demonstrate that the use of the Problem-Based Learning model assisted by flashcards is effective in enhancing students’ conceptual understanding of IPAS. Therefore, this model can be considered a viable alternative for teaching IPAS in elementary schools.